Konflik Keluarga dan Dampak Terhadap Psikologis Anak - Amalia Ramadhani; Ellen Prima (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Family conflict is a common issue in household life and can significantly affect children's psychological development. The family, which should serve as a source of security, affection, and emotional support, may become a source of stress when prolonged conflicts occur. This study aims to analyze the forms of family conflict and their impact on children's psychological well-being through a library research approach. The study employs a descriptive qualitative method by examining various scientific journals, books, research articles, and relevant literature. Data were collected through literature identification, selection, and review, then analyzed using content analysis techniques. The findings indicate that children who grow up in conflict-ridden families are more likely to experience anxiety, stress, depression, low self-esteem, social difficulties, and decreased academic performance. Family conflict also affects children's emotional stability, social relationships, and personality development. Therefore, healthy communication, positive parenting practices, and adequate emotional support from parents are essential to minimize the negative effects of family conflict on children's development and mental health.